Redispersible dry powders containing nanoencapsulated curcumin increase its antioxidant activity - Gundel S.D.S. (2024)
© 2024 Elsevier LtdThe present study aimed to develop redispersible spray-dried powders containing curcumin-loaded Eudragit® L100 nanocapsules and evaluate their physicochemical properties and antioxidant potential. The spray drying process showed a yield of over 85%, low residual moisture content (<2%), and all the physicochemical characteristics of the nanocapsules were recovered after the aqueous redispersion of the dry powders. In addition to the dry powders, the following samples were also analyzed: pure curcumin, pure lactose, and curcumin-lactose mix. In TGA and DSC analysis, all samples were thermostable and exhibited no chemical interactions with each other. In FTIR analysis, the nanostructured powder system showed functional groups of the precursors (curcumin and lactose), confirming the effectiveness in the preparation of the nanostructured material. In the evaluation of the free radical scavenging activity of DPPH•, the dry powder containing nanoencapsulated curcumin showed antioxidant activity approximately six times higher than free curcumin. Therefore, spray drying of nanoencapsulated curcumin made it possible to obtain a dry powder with homogeneous aqueous redispersion, as well as promoting the potentiation of the antioxidant activity of curcumin.